Differential effects of thiamine, BAP, and thidiazuron combinations on shoot multiplication and phenolic-flavonoid accumulation in pineapple in vitro cultures - Rachman, Dinda Septia; Suminar, Erni; Nuraini, Anne; Wicaksono, Fiky Yulianto; Amien, Suseno; Mubarok, Syariful; Hermanto, Hermanto (Universitas Padjadjaran, 2026)
The demand for high-quality pineapple (Ananas comosus (L.) Merr.) planting materials continues to increase, while conventional propagation methods are limited in multiplication rate, uniformity, and production efficiency. In vitro culture offers an alternative approach for rapid and large-scale seedling production. However, information on the effects of thiamine and cytokinin combinations on both shoot multiplication and phenolic-flavonoid accumulation in pineapple in vitro remains limited. This study evaluated ten defined combinations of thiamine and cytokinin for shoot multiplication and total phenolic-flavonoid contents of pineapple explants. The experiment employed a completely randomized design with 10 treatment combinations of thiamine (0.1 and 0.4 mg/L), cytokinin TDZ (0.01 and 0.1 mg/L) and BAP (1 and 2 mg/L) with three replications. The combination of 0.1 mg/L thiamine and 1 mg/L BAP produced the highest number of shoots (3.33 shoots) and leaves (17.56 leaves). In contrast, 0.4 mg/L thiamine combined with 0.1 mg/L resulted in the earliest shoot emergence (54.67 day after subculture) and the highest total phenolic content (13.62 mg GAE/g DW) and total flavonoid content (15.41 mg QE/g DW). No visible browning symptoms were observed in this treatment. These findings demonstrate that the optimal culture conditions differed according to the intended objective, 0.1 mg/L thiamine with 1 mg/L BAP favored shoot proliferation and leaf development, whereas 0.4 mg/L thiamine with 0.1 mg/L TDZ favored phenolic and flavonoid accumulation.